Oral and Maxillofacial Surgery – the future is in our collective hands. Re: Editorial: Our specialty, our future, is the writing on the wall?. Issue 1 (January 2022) - Woolley, E.
Abstract: We offer a response to the Editorial 'Our Specialty, Our Future, Is the Writing on the Wall?' by Newman et al and suggest opportunities to support recruitment, retention and education in Oral and Maxillofacial Surgery.